What's in a name: putting the skills of librarianship back into circulation. (September 2014) - Brice, Anne; Grant, Maria J.
Abstract Anne Brice, recipient of the 2014 Cyril Barnard Memorial Prize, reflects on the themes of names and skills of the health library and information professions. She questions whether service users share the same concerns of librarians that this nomenclature is too narrow and too closely associated with the buildings that provide its name. She proposes that in mediation between the users and their required knowledge sits a unique opportunity to place the profession in the centre of knowledge translation.